Simultaneous Allocation of Bundled Goods through Auctions: Assessing the Case for Joint Bidding. (12th August 2015) - Rondeau, Daniel; Courty, Pascal; Doyon, Maurice
Abstract : We study the costs and benefits of allowing joint bidding in multiple simultaneous first price sealed bid auctions for bundled goods with private values. Joint bidding raises the prospect of higher allocative efficiency but also reduces the number of bidders, resulting in an ambiguous net impact on seller revenue. The research was carried out using laboratory experiments in which groups of up to six buyers competed for eight bundles of two separable goods each. The main results show that in our experimental environment, allowing joint bidding increases efficiency by 11.3% and revenue by 9.4%. The research has immediate applications to the sale of public forest stands that arbor a mixture of species. For this reason, we explore how the results are affected by excess supply, the presence of dominant firms, and the removal of an allocation rule requiring multiple bidders under certain circumstances.